A tale of two economies: Diachronic comparative analysis of diverging paths of growth and inequality in the United States and the United Kingdom - Panagiotis Karountzos; Nikolaos T. Giannakopoulos; Damianos P. Sakas; Stavros P. Migkos (Economies, 2024)
This study investigates the correlation between the Gini index and gross domestic product (GDP) in two of the world's largest capitalist economies: the United States and the United Kingdom. Utilizing econometric methods, including stationarity tests and linear regression, this research work aims to elucidate the relationship between economic inequality and economic growth. The results for the United States reveal a significant positive correlation between GDP and the Gini index, suggesting that economic growth is associated with rising income inequality. In contrast, the United Kingdom shows a much weaker relationship, indicating that other factors, such as redistributive policies and social welfare programs, may mitigate the impact of economic growth on income inequality. These findings highlight the importance of national policies and institutional frameworks in shaping economic outcomes and can be used in policy making. This study contributes to the existing literature by providing a comparative analysis of the correlation between GDP and the Gini index in two major capitalist economies, offering fresh empirical insights.
Keywords: 330; economic inequality; Gini index; GDP; growth; comparative analysis; time series; regression analysis